Influence of enzymatic devulcanization process conditions on the tensile strength of revulcanized rubber - Othman, Emeliana; Yusof, Faridah; Azmi, Azlin Suhaida (Penerbit Akademia Baru, 2017)
Rubber based product has properties very different from the viscous latex of the rubber tree, Hevea brasiliensis. The properties of rubber latex are usually changed to enable it be used in production of many rubber based products such as tires, hoses, and etc. To strengthen it, the rubber undergoes vulcanization process where the addition of sulfur and heating the mixture under pressure is done which results in the formation of sulfur-bridges between the hydrocarbon chains. It makes an economic sense to recycle spent rubber products. Prior to recycling, surface devulcanization of rubber is vital to produce the acceptable reprocessed product. Devulcanization is basically a process that cleaved the monosulfidic, disulfidic or polysulfidic of vulcanized rubber. The tensile strength of the new material is of paramount important. In this study, enzymatic devulcanization of rubber was performed. Design of Experiment and analysis was conducted using Design Expert® (Version 6.0.8) software, with a tensile strengths as the responses. Results showed that both factors tested, time of incubation and rubber concentration contributed significantly towards the strength of rubber products. Data shows that setting the incubation time for 4 hours with 4% w/v rubber in the incubation media results in the highest tensile strength of 10.7 MPa, an increase of 67% from the untreated control. In conclusion, the process conditions of the enzymatic devulcanization of used rubber product have been successfully optimized using tetrathionate hydrolase rich media, produced by Thiobacillus ferrooxidans. This information is important to improve enzymatic devulcanization method and finally to increase the percentage of rubber recycling.